Impact of Resistance and Endurance Exercise Training on Heart Rate Variability - Dr Rakesh Yeole, Dr Devendra Ghodpage, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The “Heart rate variability (HRV) test is a non-invasive way to check the hearts and autonomic nervous system (ANS) overall health and performance. The test finds the average and standard deviation of the time between heartbeats. Aim: The goal of this 12-week trial is to find out how different types of exercise, including resistance and endurance training, affect people's HRV. Autonomic control and cardiovascular health will be the primary outcomes of the study.